Investigating The Role of the use of computer Hardware , software and lecturer involvement on online universities student satisfaction - Agus Purwanto; Tawar Tawar (UJoST- Universal Journal of Science and Technology, 2024)
The purpose of this study is to investigate the role of the use of computer hardware in online learning has a positive effect on online student satisfaction, investigate the role of The use of computer software in online learning has a positive effect on online student satisfaction and investigate the role of Lecturer involvement in online learning has a positive effect on student satisfaction learning online. This research will use exploratory descriptive method. This means that the research will begin by providing an overview about each variable studied descriptively, then study the relationship pattern and its influence exploratively. Based on the formulation of the problem and objectives to be achieved, this study uses a survey method. In taking the sample, the researcher used a sample of level 1 and 2 students filled out the Google Form questionnaire as many as 168 people. Because learning is online, the distribution of questionnaires is also carried out using existing technological facilities using Google Drive with the Google Form application. In this case, SEM with SmartPLS is an alternative technique in SEM analysis. The data used does not have to be multivariate normal distribution. In SEM with SmartPLS the value of the latent variable can be estimated according to the linear combination of the manifest variables associated with a latent variable and is treated to replace the manifest variable. According to Monecke & Leisch (2012) in Sarwono and Narimawati (2015), SEM with SmartPLS consists of 2 components, namely: (1) Inner Model and (2) Outer Model.The results of data processing with SmartPLS show that The use of computer hardware in online learning has a positive effect on online student satisfaction, The use of computer software in online learning has a positive effect on online student satisfaction, Lecturer involvement in online learning has a positive effect on student satisfaction learning online